PEUYEM KOROTO: PEWARISAN MAKANAN TRADISIONAL DAN NILAI-NILAI KARAKTER MASYARAKAT DESA CIPARIGI - Hasni Hasan; Fauzi, Akhmad Rizky; Rahmah Hidayah; Muhammad Saleh Qadri; Amniar Ati (Tambo: Journal of Manuscript and Oral Tradition, 2024)
This article describes the traditional food in Ciparigi Village, a type of tape (peuyeum).  Peuyeum as a traditional food has different uniqueness in each region. The people of Ciparigi Village have their own uniqueness in making peuyeum. The glutinous rice that has been boiled is then wrapped using dukuh leaves to resemble a koroto / kroto / krangge anthill so it is called peuyeum koroto. The existence of peuyem koroto has now begun to experience marginalisation in the community. In addition to the description of the making, this study reviews the character meanings contained in peuyem koroto including religious values, environmental care, and creativity. The implication of this study is that the universal religious values and environmental awareness need to be maintained and campaigned more massively. In addition, the idea of creativity of peuyum makers needs to be supported by many parties, especially in promotion and marketing.